Penebusan Rut Oleh Boas Sebagai Tipologi Penebusan Kristus Dan Refleksi Bagi Teologi Misi Masa Kini - Ruat Diana; Sonny Eli Zaluchu; Deni Triastanti (Sekolah Tinggi Teologi Bethel Ambon, 2020)
This article deals with Boaz's redemption of Ruth as an Old Testament typology in explaining Christ's redemption in the New Testament. The formulation of the research problem is how is the relationship between the redemption of Ruth in the Old Testament and the redemption of Christ and the reflection of today's mission theology? The author uses historical methods (Historical Research) and descriptive methods (Descriptive Research), namely literature studies through supporting books and journals, regarding the redemption of Ruth by Boaz in the Old Testament and explaining Christ's redemption in the New Testament. From the context of redemption (go'el) in the Old Testament, the redeemer must have more ability or strength than someone who is redeemed. Because people who are redeemed are often described as weak or slave. Meanwhile, the context of redemption in the New Testament was immediately carried out by the Lord Jesus Christ through Christ's death on the cross and His resurrection to reveal redemption to all tribes, nations, who exist on earth as weak and sinful creatures, which is also the basis of mission theology for the message. The gospel for all sinners. The redemption made by Christ is not only for one tribe of Israel, but all people have the same right to salvation and redemption to live in union with Christ. Artikel ini membahas tentang penebusan Rut oleh Boas sebagai tipologi Perjanjian Lama dalam menjelaskan penebusan Kristus dalam PerjanjianBaru. Rumusan masalah penelitian ini adalah bagaimana kaitan penebusan Rut dalam Perjanjian Lama dan penebusan Kristus dan refleksi teologi misi masa kini? Penulis menggunakan metode historis (Historical Research) dan metode deskriptif (Descriptive Research) yaitu studi pustaka melalui buku-buku dan jurnal yang mendukung, tentang penebusan Rut oleh Boas dalam Perjanjian Lama dan menjelaskan penebusan Kristus dalam Perjanjian Baru. Dari konteks penebusan (go’el) di dalam Perjanjian Lama,penebusharus memiliki kemampuan atau kekuatan lebih dari seseorang yang ditebus. Karenaorang yang ditebussering digambarkan sebagai orang yang lemah atau budak. Sedangkan konteks penebusan di dalam Perjanjian Baru langsung dilakukan Tuhan Yesus Kristus melalui kematian Kristus di kayu salib dan kebangkitan-Nya untuk menyatakan penebusan kepada semua suku, bangsa, yang ada di bumi sebagai mahkluk yang lemah dan berdosa, yang sekaligus sebagai dasar teologi misi bagi pekabaran Injil bagi semua manusia berdosa. Penebusan yang dilakukan oleh Kristus bukan hanya kepada satu suku Israel saja, tetapi semua orang memiliki hak yang sama untuk mendapatkan keselamatan dan penebusan untuk hidup bersatu dengan Kristus.